Customer Satisfaction: Between Expectation and Reality of Service Quality in Container Depot, Surabaya: Kepuasan Pelanggan: Antara Harapan dan Kenyataan Kualitas Layanan di Terminal Kontainer, Surabaya - Ristanti Akseptori; Medi Prihandono; Danis Maulana; Lestari Mulyani Ningsih (Universitas Muhammadiyah Sidoarjo, 2025)
Improving service quality is a must for any company to cope with the high market demand. It is also a concern for shipping services companies. Quality is the benchmark for innovation among freight transportation business service providers to gain customer satisfaction. This research was conducted at a shipping service company that has several subsidiaries. One of which manages container depots in the Surabaya area. The change in the Depot concept caused Depot services to change, and customers felt a different impact. The effect of these changes made customers complain about the services provided by the Depot. This study aimed to determine the difference between expectations and reality of the services provided to determine the customer satisfaction of Container Depot in Surabaya using the SERVQUAL method. The sample is 70 customers of the 228 population. The research results showed that all attributes had negative gap values, which means that the customer was dissatisfied. The research gap is that this research was limited to SERVQUAL application in the niche sector of container depot services within the shipping industry. This creates a gap in understanding the unique challenges and service quality expectations. Therefore, the Depot must improve its service quality for each attribute and give more concern to the highest negative gap value (empathy, reliability, responsiveness, tangibility, and assurance). The implication of the research revealed that the depot must adapt their service quality to align with customer expectations and prioritize service improvement through staff training, enhancing communication with customers, and streamlining operational processes.